Preoperative pain associated with peribulbar injection for cataract surgery - Gupta, Isha; Sachdeva, Abhishek; Goel, Tushar; Pradhan, Nitesh; Singh, Komal (International Journal of Research in Medical Sciences, 2018)
Background: Patients admitted for cataract surgery have a fear of worst pain due to peribulbar injection for anaesthesia rather than surgery itself. The aim of this study is to find out the threshold of pain associated with the anaesthetic peribulbar injection for cataract surgery. Methods: This prospective randomised study was carried out at Ophthalmology department of Maharishi Markandeshwar University from 10 January 2017 to 22 March 2017. 100 patients undergoing elective cataract surgery were administered a peribulbar block. Before injection all patients were briefed about the procedure and counselled regarding the degree of pain that they may experience. Patients were asked to grade the pain of peribulbar anaesthetic injection, using a Visual Analogue Scale (VAS). Results: Focus of the study was on the degree of pain associated with anaesthetic peribulbar injection for cataract surgery. 100 patients (60 males and 40 females) were included in the study. 90 (90%) patients were having their first surgery, they were more apprehensive especially about the injection associated pain. 10 (10%) patients with history of previous cataract surgery were calm, confident and claimed that they felt no pain at all. 92 (92%) patients had just needle prick lead to heaviness or mild pain. Only small percentage of patients i.e. 8 (8%) had injection associated moderate to severe pain. Conclusions: The study revealed that the peribulbar anaesthesia for cataract surgery is safe and highly effective. The degree of pain associated with peribulbar injection is much less than what the patients actually have in their mind and fear of. The study also shows ‘pain threshold’ and anxiety level as major factors for pain perception.